The effects of psychosocial stimulation on the development, growth, and treatment outcome of children with severe acute malnutrition age 6-59 months in southern Ethiopia: a parallel group cluster randomized control trial (EPSoSAMC study) - Tesfalem T. Tessema; Andamlak G. Alamdo; Tewodrose G. Yirtaw; Fana A. Deble; Eyoel B. Mekonen; Teklu G. Abessa; Tefera B. Lema (BMC, 2019)
Abstract Background Severe Acute Malnutrition (SAM) remains a major cause of child mortality. To improve the management and survival of children the World Health Organization (WHO) endorsed the protocol for the management of SAM. The protocol suggested the integration of psychosocial stimulation as part of the medico-nutritional care process to prevent the long-term adverse developmental impact of the SAM. However, there is little scientific evidence behind the recommended stimulation intervention. Method A parallel-group cluster-randomized controlled trial will be conducted among 144 children with SAM age 6-59 months in Southern Ethiopia. The study will have two groups where: children with SAM admitted in the intervention health facilities will receive psychosocial stimulation in addition to the routine inpatient care and for 6 months after discharge. Children with SAM admitted in the SC of the control health facilities will receive the routine inpatient care without psychosocial stimulation and home-based follow up for 6 months after discharge. All mothers/ caregivers will also receive uniform health education on child health-related issues. The primary outcome of the study will be child development while the secondary outcomes will include child growth and treatment outcome. All outcomes will be assessed four times: at enrollment, upon discharge from the SC, at 3 and 6 months of follow up. The data will be analyzed using STATA Version 15 Statistical Software. The anthropometric Z-scores and percentile of the median will be calculated child using WHO Anthro Version 3.2.2 Statistical Software. To assess the overall effect of the intervention by controlling other potential contributing factors, a generalized linear mixed model will be used. Discussion The present study will have an important contribution in generating supplementary evidence regarding the effect of psychosocial stimulation interventions on the development and growth outcomes of children with SAM. The study will further address the impact of the intervention on treatment outcome indicators that are still under-researched areas requiring new scientific evidence. Trial registration Pan African Clinical Trials Registry -PACTR201901730324304. Registered 25 November 2018, https://pactr.samrc.ac.za/TrialDisplay.aspx?TrialID=5739